FashioNordic : Folk costume as performance of genealogy and place - Gradén, Lizette (Journal of Folklore Research, 2014)
This article elaborates on the embodiment of heritage via dressing practices in several rural and urban Nordic communities in the United States. Getting dressed is a shared human practice that we engage in and repeat most days, and for special occasions, traditional dress, or folk costume, comes into particular focus. I approach dressing in folk costume as a “situated embodied practice,” a mode of performance that exposes the way value judgments of the body are informed by societal notions of dress, with body and dress understood as socially constructed entities that shape each other. Based on attention to an embodied heritage that women create, make, view, discuss, and wear, I suggest that folk costumes from Sweden and its neighboring countries are increasingly individualized in the United States; that traditional dress is in fashion; and that garments, patterns, materials, and designs are used to illustrate complex family trees, places of belonging, and key experiences in life.
Publisher Copyright: © 2014 Department of Folklore and Ethnomusicology, Indiana University.